2015
DOI: 10.1186/s12891-015-0676-1
|View full text |Cite
|
Sign up to set email alerts
|

Influence of pelvic incidence-lumbar lordosis mismatch on surgical outcomes of short-segment transforaminal lumbar interbody fusion

Abstract: BackgroundThe importance of pelvic incidence-lumbar lordosis (PI-LL: PI minus LL) mismatch is emphasized in long-segment fusion for adult spinal deformity; however, there are few studies evaluating the influence of PI-LL on surgical outcomes after short-segment fusion. In this study, we have examined the effects of PI-LL mismatch on surgical outcomes of short-segment lumbar intervertebral fusion for lumbar degenerative diseases.MethodsPatients with lumbar degenerative disease treated by short-segment (1 or 2 l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
118
1
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 145 publications
(127 citation statements)
references
References 25 publications
4
118
1
4
Order By: Relevance
“…Since pelvic incidence is set by adulthood, corrective surgeries should be planned on achieving the appropriate lumbar lordosis. 11 It has been reported that patients with AS had lower pelvic incidence, lumbar lordosis, sacral slope and higher pelvic tilt and sagittal vertical axis when compared to healthy controls. 7,12 Sagittal vertical axis, lumbar lordosis and sacral slope were suggested as predictive factors for the clinical outcomes in AS.…”
mentioning
confidence: 97%
“…Since pelvic incidence is set by adulthood, corrective surgeries should be planned on achieving the appropriate lumbar lordosis. 11 It has been reported that patients with AS had lower pelvic incidence, lumbar lordosis, sacral slope and higher pelvic tilt and sagittal vertical axis when compared to healthy controls. 7,12 Sagittal vertical axis, lumbar lordosis and sacral slope were suggested as predictive factors for the clinical outcomes in AS.…”
mentioning
confidence: 97%
“…8,10 For deformity surgery, restoring pelvic incidence-lumbar lordosis mismatch to less than 10° had a great impact on improving clinical performance scores. 1,16,19 Little is known about the effects of MIS-TLIF with expandable interbody devices on pelvic parameter measurements assessed on lateral radiographs. In light of this, we performed a retrospective review to evaluate the effects of MIS-TLIF with expandable versus static interbody devices on disc height, foraminal height, index-level segmental lordosis, lumbar lordosis, and pelvic parameters.…”
mentioning
confidence: 99%
“…Op CD-1Y patients also showed greater T1S-CL deformity compared to the NonOp group (74.4 %), and there was a worsening of T1S-CL mismatch from baseline to 1-year post-operative among Op CD-1Y patients (24.35°-31.41°). As PI-LL mismatch has been previously reported to influence post-operative residual symptoms, it is possible that abnormal T1S-CL could represent a similar degenerative process in the cervicothoracic junction and marker for overall deformity and imbalance [21]. T1S-CL mismatch has also been correlated with inferior patient-reported outcomes by Lee et al, an observation which is sustained in this report [9].…”
Section: Discussionmentioning
confidence: 64%